Adaptive Management of Sports Facilities Under Budget Constraints to Boost Student Achievement - Habillah Safira Akmalina; Tsania Dinda Fahira; M Faiq Ahsani; Siti Nur Hidayah; Irwanto (Journal of Educational Management Research, 2026)
This study aims to examine how sports facilities and infrastructure are managed under budget constraints to support student achievement. The research employs a qualitative descriptive approach, focusing on the strategic management of planning, procurement, utilization, and maintenance processes. Data were collected through in-depth interviews with facility managers and analysis of official student competition records. The findings indicate that management practices emphasize priority-based planning, adaptive maintenance strategies, and optimization of existing facilities rather than expansion. Procurement is conducted through formal e-procurement procedures, while utilization is facilitated by a digital booking system that enhances accessibility. Maintenance is performed selectively due to limited budgets, often requiring a single vendor to manage multiple locations. These results suggest that effective management under fiscal constraints relies on strategic prioritization and resource optimization to sustain student performance. Although budget limitations restrict expansion and comprehensive maintenance, adaptive strategies enable facilities to continue supporting student athletic development.